Emotive Language Function As A Medium To Motivate Students - Kadek Adyatna Wedananta; I Putu Yudi Sudarmawan (Widya Accarya, 2023)
This study seeks to explore the emotive functions of language as a medium to motivate students. This study employed a qualitative methodology. This research was conducted in schools located in Denpasar, Bali, with teachers as its subjects to interview. Based on the findings of interviews with all participants, observations, and documentation, it can be inferred that the emotive function of language contributes to student motivation in the following ways: The emotive function of language is essential for motivating students; for example, teachers must express pride when students answer questions correctly; teachers must display enthusiasm while responding to anything students do in the classroom; teachers must demonstrate empathy when students answer incorrectly, but they must also keep students in a good mood and avoid letting them down; and teachers must express support when students are about to give up on answering a question.